Arctic biogeochemical and optical properties of dissolved organic matter across river to sea gradients - Michael G. Novak; Antonio Mannino; J. Blake Clark; Peter Hernes; Maria Tzortziou; Robert G. M. Spencer; Anne M. Kellerman; Brice Grunert (Frontiers in Marine Science, 2022)
Arctic landscapes are warming and becoming wetter due to changes in precipitation and the timing of snowmelt which consequently alters seasonal runoff and river discharge patterns. These changes in hydrology lead to increased mobilization and transport of terrestrial dissolved organic matter (DOM) to Arctic coastal seas where significant impacts on biogeochemical cycling can occur. Here, we present measurements of dissolved organic carbon (DOC) and chromophoric DOM (CDOM) in the Yukon River-to-Bering Sea system and two river plumes on the Alaska North Slope which flow into the Beaufort Sea. Our sampling characterized optical and biogeochemical properties of DOM during high and low river discharge periods for the Yukon River-Bering Sea system. The average DOC concentration at the multiple Yukon River mouths ranged from a high of 10.36 mg C L -1 during the ascending limb of the 2019 freshet (late May), 6.4 mg C L -1 during the descending limb of the 2019 freshet (late June), and a low of 3.86 mg C L -1 during low river discharge in August 2018. CDOM absorption coefficient at 412 nm ( a CDOM (412)) averaged 8.23 m -1 , 5.07 m -1 , and 1.9 m -1 , respectively. Several approaches to model DOC concentration based on its relationship with CDOM properties demonstrated cross-system seasonal and spatial robustness for these Arctic coastal systems despite spanning an order of magnitude decrease in DOC concentration from the lower Yukon River to the Northern Bering Sea as well as the North Slope systems. “Snapshot” fluxes of DOC and CDOM across the Yukon River Delta to Norton Sound were calculated from our measurements and modeled water fluxes forced with upstream USGS river gauge data. Our findings suggest that during high river flow, DOM reaches the delta largely unaltered by inputs or physical and biogeochemical processing and that the transformations of Yukon River DOM largely occur in the plume. However, during low summer discharge, multiple processes including local precipitation events, microbial decomposition, photochemistry, and likely others can alter the DOM properties within the lower Yukon River and Delta prior to flowing into Norton Sound.